2018
DOI: 10.1186/s12906-018-2138-4
|View full text |Cite
|
Sign up to set email alerts
|

Zanthoxylum armatum DC extracts from fruit, bark and leaf induce hypolipidemic and hypoglycemic effects in mice- in vivo and in vitro study

Abstract: BackgroundZanthoxylum armatum DC is an important medicinal plant of south East Asia, and has been used to treat various ailments in traditional medicine including diabetes. This study investigated the in vitro and in vivo antidiabetic and biochemical effects of extracts of Z. armatum in mice.MethodThe extracts of fruit, bark and leaf from Z. armatum were tested for α-glucosidase inhibition activity. Albino mice of either sex weighing (26–30 g) assigned into groups. Diabetes was induced by IP injection of allox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Although the popularity of Z. bungeanum as a condiment is relatively low outside of China, its medicinal value merits attention. This species has been used as an ancient herbal medicine in China, and its pericarp shows anti-inflammatory and anti-bacterial activities [2], relieves arthritis [3], protects against gastric mucosal damage [4], lowers blood lipid levels [5], regulates antithrombotic effects [6], and enhances immunity [7]. A recent study found that collagen extracted from Z. schinifolium exerts positive anti-tuberculosis effects [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the popularity of Z. bungeanum as a condiment is relatively low outside of China, its medicinal value merits attention. This species has been used as an ancient herbal medicine in China, and its pericarp shows anti-inflammatory and anti-bacterial activities [2], relieves arthritis [3], protects against gastric mucosal damage [4], lowers blood lipid levels [5], regulates antithrombotic effects [6], and enhances immunity [7]. A recent study found that collagen extracted from Z. schinifolium exerts positive anti-tuberculosis effects [8].…”
Section: Introductionmentioning
confidence: 99%
“…3a), both of which utilize glycolysis to obtain the initial substrate for producing dimethylallyl diphosphate (dimethylallyl-PP). Then, dimethylallyl-PP is used to generate monoterpenoids, diterpenoids, triterpenoids, and other terpenoid compounds [14], which are the main aromatic substances involved in the special numbing taste in the fruits of Z. armatum [10]. In the present study, the results showed that almost all genes involved in terpenoid backbone biosynthesis were differentially expressed genes and detected at significant levels in the fruit samples ( Fig.…”
Section: Identification and Characterization Of Genes Involved In Termentioning
confidence: 49%
“…More than 140 components related to aromatic compounds and fatty acid biosynthesis have been gradually identified in different tissues of Z. armatum [9]. Various terpenoid substances are among the main components associated with the numbing taste of Z. armatum, including linalool (29.30%), limonene (14.30%), myrcene (6.02%), cineole (1.32%) and so on [7,10]. Terpenoids are a large category of necessary secondary metabolites in plants, includingmonoterpenes, diterpenes, sesquiterpenes, triterpenoids and other terpenoid-quinone compounds [11].…”
Section: Introductionmentioning
confidence: 99%
“… Tejohva/Tejovati (S), Tejbal (H), Yellow wood Tree timaru (L) Shrub (W)/bark fruit and root Essential oil (mainly contains linalool and limonene), armatamide [ 90 ] One teaspoon powder of roots or stems is taken twice a day for 1 month Methanol extracts of the fruits, leaves and bark showed α-glucosidase inhibitory activity in vitro. All the extracts at 500 mg/kg for 15 days were found to decrease fasting blood glucose levels in ALX induced diabetic mice [ 91 ] Saxifragaceae Bergenia ciliata (Haw.) Sternb.…”
Section: Resultsmentioning
confidence: 99%
“…ex RoyleAtivisha (A/S), Atish (H), Indian Atish (E)Herb (C)/rootsAatisine, dihydroatisine, hetisined, heteratisine, 12-secohetisan-2-ol, N -succinoylanthranilate, atesinol 6-benzoylheterastine, N -diethyl- N -formyllaconitine, methyl aconitine, aconitine, anthorine [84]The powder of Atish roots, Ajuga parviflora leaves and Podophyllum hexandrum roots is given twice a day (half teaspoonful) early in the morning and at night after meals up to 3 monthsThe oral administered of methanol root extract (200 mg/kg/day for 28 days) increased the levels of plasma glycoproteins and also decreased the level of sialic acid and elevated levels of hexose, hexosamine and fructose in the liver and kidney of STZ induced diabetic rats [85]Rosaceae Rubus ellipticus Sm.Golden/yellow Himalayan raspberry (E), Hinsar/Hisalu (L)Shrub (W)/fruits and rootsGallic acid, catechin, chlorogenic acid ( 18 ), caffeic acid [86]One teaspoon powder of roots is taken twice a day for 1 monthThe petroleum ether, ethanol and aqueous extracts of fruits (200 mg/kg each) exhibited antidiabetic activity using GTT in ALX induced diabetes rats [87]Rubiaceae Rubia cordifolia L.Aruna (S), Manjistha (A), Manjeeth/Majith (H), Indian madder (E), Charchora (L)Climber (C)/rootsCordifoliol, cordifodiol, rubiacordone, purpurin, alizarin [88]The infusion (25 mL) of roots is taken once a day for 40 daysThe oral administration of aqueous root extract (1 g/kg/day for 8 weeks) showed an anti-hyperglycemic effect in STZ induced diabetic rats [89]Rutaceae Zanthoxylum armatum DC.Tejohva/Tejovati (S), Tejbal (H), Yellow wood Tree timaru (L)Shrub (W)/bark fruit and rootEssential oil (mainly contains linalool and limonene), armatamide [90]One teaspoon powder of roots or stems is taken twice a day for 1 monthMethanol extracts of the fruits, leaves and bark showed α-glucosidase inhibitory activity in vitro. All the extracts at 500 mg/kg for 15 days were found to decrease fasting blood glucose levels in ALX induced diabetic mice [91]Saxifragaceae Bergenia ciliata (Haw.) Sternb.Pashanabheda (S), Patharchat (H), Hairy Bergenia (E)Herb (W)/whole plantBergenin Bergenin, catechin, gallic acid, tannic acid [92]Decoction (half cup) of aerial parts is taken before breakfast(...…”
Section: Resultsmentioning
confidence: 99%